Using Soft Systems Methodology for Computer Game Design. - Taylor, M. J.; Baskett, M.; Hughes, G. D.; Wade, S. J. (Systems Research & Behavioral Science)
The writers explore how soft systems methodology (SSM)—a well-established approach for developing systems to diagnose and assist comprehension of complex organizational problems—can benefit the initial identification and communication of new computer game concepts. They demonstrate the use of the primary elements of mode 1 of SSM—rich pictures, root definitions, the CATWOE framework, and conceptual designs—in a theoretical application to the design of well-known existing computer games. They conclude that SSM can provide an overview of the world of computer games and that the detailed creation of the code, artistry, music and sound effects can emerge from this platform.